2004
DOI: 10.1021/jf034429w
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Interactions between Chitosan and an Anionic Surfactant

Abstract: Chitosan is a cationic biopolymer that has many potential applications in the food industry because of its unique nutritional and physiochemical properties. Many of these properties depend on its ability to interact with anionic surface-active molecules, such as phospholipids, surfactants, and bile acids. The purpose of this study was to characterize the interaction between chitosan and a model anionic surfactant (sodium dodecyl sulfate, SDS) using isothermal titration calorimetry (ITC), surfactant-selective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 16 publications
(30 reference statements)
4
92
0
4
Order By: Relevance
“…38,42,[158][159][160][161][162][163][164] It was shown that SDS and chitosan form insoluble complexes well below the cmc of the surfactant and in a high polyelectrolyte excess, indicating a strong cooperative behavior ascribed to the hydrophobic interactions among the bound surfactant molecules. 38,160 In the work done by our group we also found that chitosans with different molecular weights and different degrees of acetylation (DA) (from ca. 2% to 15%) mixed with SDS, sodium dodecyl benzene sulphonate (SDBS) and sodium lauryl ether sulphate with an average of 2 ethylenoxide units per surfactant (SLES) form insoluble complexes over a wide range of mixing ratios and concentrations.…”
Section: Chitosanmentioning
confidence: 99%
“…38,42,[158][159][160][161][162][163][164] It was shown that SDS and chitosan form insoluble complexes well below the cmc of the surfactant and in a high polyelectrolyte excess, indicating a strong cooperative behavior ascribed to the hydrophobic interactions among the bound surfactant molecules. 38,160 In the work done by our group we also found that chitosans with different molecular weights and different degrees of acetylation (DA) (from ca. 2% to 15%) mixed with SDS, sodium dodecyl benzene sulphonate (SDBS) and sodium lauryl ether sulphate with an average of 2 ethylenoxide units per surfactant (SLES) form insoluble complexes over a wide range of mixing ratios and concentrations.…”
Section: Chitosanmentioning
confidence: 99%
“…This possibility was tested using a bile acid, taurocholic acid. Bile acids are cholesterol derivatives; previous reports have shown adsorption by chitosan (32,33). Following incubation of freeze-dried spores with 3 mM taurocholic acid solution, the residual amount of taurocholic acid was measured by HPLC and used to calculate removal by spores.…”
Section: The Presence Of Chitosan and Removal Of The Dityrosine Layermentioning
confidence: 99%
“…Interfacial engineering could be used to improve the stability of oil-in-water emulsions against environmental stresses or to create emulsions with novel functional properties. Emulsions stabilized by multilayered membranes, such as chitosan, whey proteins, pectin, and carrageenan, were recently studied by McClements et al, and their results indicated improved emulsion stability against pH, ionic strength, thermal processing, and freezing [1,2,[6][7][8][9][10][11][12]. Among them, β-lactoglobulin and Κ-carrageenan were found to be an interesting biopolymer pair to prepare stable O/W emulsions [12].…”
Section: Introductionmentioning
confidence: 99%